Long-term visual outcome in patients treated by flow diversion for carotid-ophthalmic aneurysms. (23rd March 2018) - Touzé, Romain; Touitou, Valérie; Shotar, Eimad; Gabrieli, Joseph; Drir, Mehdi; Mathon, Bertrand; Sourour, Nader-Antoine; Clarençon, Frédéric
Abstract : Background: Flow-diverter stents (FDSs) are an upgrade in the treatment of intracranial aneurysms. However, complications concerning covered branches have been reported, especially the ophthalmic artery (OA). The purpose of our study was to evaluate the long-term ophthalmic complication rate of carotid-ophthalmic aneurysms (COA) without visual pathways compression, treated by a FDS covering the OA by performing an exhaustive ophthalmic examination. Material and methods: Retrospective analysis of a single-center database screening the patients treated from October 2009 to April 2015 for an intracranial aneurysm with a FDS. The patients treated for a non-compressive COA with coverage of the OA by the device were studied (n=30). Among these patients, 15 (50%) were excluded. The remaining 15 patients underwent a systematic and extensive ophthalmic examination at least 2 years after the stent placement by two ophthalmologists. Results: Fifteen patients with 16 COAs treated with a FDS were included. Mean follow-up was 4.1±2 years. Six patients (40%), presented ophthalmic complications, including three fugax amauroses (18.8%) and four significant visual field defects (25%). After comparing each eye's visual field's patients, we observed a significant difference between the eye on the FDS side compared with the contralateral eye, with a mean deviation of −1.58 dB versus −0.67 dB respectively (P=0.003). Visual acuity was preserved in all patients. Conclusion: Patients treated by FDS for COA have a good long-term clinical ophthalmic outcome. However, extensive ophthalmic examination shows a high percentage of minor ophthalmic modifications. Interventional neuroradiologists should be aware of these possible complications when choosing to treat these aneurysms with FDS.